Training on the Use of Artificial Intelligence (AI) Technology to Support the Learning and Teaching Process - Kartubi, Kartubi; Rapiko, Rapiko; Surayya, Eli; Mahyuzar, Mahyuzar; Husarida, Husarida (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
This community service activity was carried out by the Islamic Religious Education Study Program team of UIN Sultan Thaha Saifuddin Jambi at IAI Al-Mujaddid Sabak, Jambi City with the aim of introducing and training the use of artificial intelligence (AI) technology in the learning process. This training was attended by 20 students and 15 lecturers from various educational backgrounds. In this activity, participants were given a basic understanding of the concept and benefits of AI, as well as its application in education, especially in the context of Islamic Religious Education. Although some participants were already familiar with AI technology, they were still not used to using it practically in learning. Therefore, this training aims to increase participants' awareness, knowledge, and skills in utilizing AI as a tool to optimize the learning process. The results of this training showed that participants were very enthusiastic and actively participated, despite challenges related to access to adequate devices. This activity is expected to have a positive impact on improving the quality of education, by encouraging the integration of AI technology in the Islamic Religious Education curriculum in the future.